Measurement of the Curie temperature based on temperature dependent thermal properties. (May 2021) - Wilhelmy, S.; Zimare, A.; Zhang, Q.; Rettenmayr, M.; Lippmann, S.
Abstract: A temperature gradient evaluation method for swift determination of the Curie temperature T C based on thermal conductivity and thermal diffusivity as functions of temperature is presented. In an imposed one-dimensional temperature gradient, temperature profiles along the axis of a cylindrical sample are recorded in steady-state and transient states using a photon detector. Transient temperature profiles are evaluated by an inverse numerical method, yielding the temperature dependent thermal diffusivity with a distinct change in slope at T C . The slope of the steady-state temperature profile adjusts according to the local thermal conductivity and changes abruptly at T C . The high-resolution determination of the temperature dependent thermal properties allows the identification of T C by two independent evaluations during a single experimental run, solely relying on data of thermal conductivity and thermal diffusivity. The obtained T C excellently agrees with literature values gained by conventional methods. Graphical abstract: Unlabelled Image Highlights: General method for determining temperature dependent thermal properties. Determination of temperature dependence in a single experimental run only. Prior knowledge of the functional form of temperature dependence not required. Time efficient experimental and evaluation procedures. High resolution for simultaneous determination of Curie temperature TC.